Farmers’ Participation on Rice, Corn, and Soybeans Enhancement Production Food Self-Sufficiency Program at Juwangi District Boyolali Regency - Retno Fajar Kusdiyanti; Ravik Karsidi; Sugihardjo (Advances in Social Sciences Research Journal, 2019)
Rice, Corn, and Soybeans Enhancement Production Food Self-Sufficiency Program is the government development program in agriculture area. This program is aimed at achieving food self-sufficiency through increasing food crop production, involving the participations of rice, corn, and soybeans farmers. This research aimed at analysing the differences participation among rice, corn, and soybeans famers on food self-sufficiency program. The research took place in May to August 2019 in Juwangi district Boyolali regency as it had three commodities for the program. The research used survey approach involving 130 respondents as the sample from total population of 972 farmers. The cluster sampling technique used to determine the sample. The research used questionnaire to collect the data and t-test to analyse the data. The research showed that there was no significant participation between rice farmers and corn farmers. However, there was a significant participation between rice farmers and soybeans farmers too between corn farmers and soybeans farmers.